Proyecto de factibilidad para la creación de una empresa constructora de viviendas populares para la ciudad de Cuenca - Tello Nieto, Ángel Rolando (2010)
One of the problems that is given in our country, so that the companies are not given, it is that people that have big quantities of capitals don't invest in our country, this is because the guarantees of security are not lent that is required for the investors, in such a way that you/they look for to invest their capitals outside of the Ecuador, of there the necessity to invest in our country in the fomentation of work sources and application of valid knowledge in search of the truth. The managerial management in the city of Cuenca, it should be guided toward the satisfaction of basic necessities of the families like it is it the obtaining of an own housing, for such a reason it is that the present project focuses to the implementation of a company manufacturer. The company will be devoted to the construction of housings in which the effective demand is of 17,291 families, the offer is of 0, the production of the company will be for stages, this way in the first year, each stage will build 60 housings. The company jointly with the Juridical and Technical advisers, it will plan the area of construction of housings, inside the urban area. The investment required for the project is of 219,298.03 dollars, the 31.24% it is financed by a bank and the 68.76% with own funds, of equal he/she is formed he/she obtained a they GO positive, a relationship benefits cost of 3´242,702.04, a TIR of 212.07% and an analysis of sensibility with increment of the 40% in the costs and decrease of the 30% in the revenues. Regarding the organization of the company it will be conformed by the Presidency, Manager, Advisory Juridical, Secretary, Accountant, Department of Commercialization, Inspector, Production and the necessary personnel for the construction process.